Ratiometric and amplified fluorescence nanosensor based on a DNA tetrahedron for miRNA imaging in living cells. Issue 39 (16th September 2021) - Mo, Liuting; Liang, Danlian; He, Wanqi; Yang, Chan; Lin, Weiying
Abstract : A new nanosensor based on a DNA tetrahedron for ratiometric and amplified fluorescence imaging of intracellular miRNAs. Abstract : Enzyme-free signal amplification approaches have attracted considerable attention in the field of intracellular miRNA analysis. However, the application of nucleic acid amplification has been limited by intracellular delivery of multiple oligonucleotide components with precise stoichiometry. In this work, we propose a new DNA tetrahedron (DTN )-based sensing platform addressing the delivery and stoichiometric control of nucleic components for enzyme-free amplification. The nanosensor is composed of two DTN probes; DTN-F served as the target recognition and signal output unit, and DTN-H served as the signal amplification unit. DTNs could facilitate the cell internalization of the nucleic acid probes and protect them from nuclease degradation. In the absence of target miRNA, the fluorescent strands (F ) hybridize with the hanging sequences of DTN, and FAM and TAMRA labeled on F will be separated, blocking fluorescence resonance energy transfer (FRET). In the presence of the target miRNA, F will be displaced by the target and the hairpin structure will be restored, bringing the FRET pair into close proximity and inducing a FRET signal. Moreover, the helper strands (H ) on DTN-H could liberate target miRNA through strand displacement, which will initiate a new round of reaction, generating an amplified FRET signal. The DTN nanosensor realized sensitive and selective detection of let-7a in buffer solution and 10% FBS solution. In addition, imaging of miRNA in the different cell lines and monitoring of intracellular miRNA fluctuations were carried out The developed method offers a new tool for bioanalytical and biomedical research.